Combined effect of bending and flattening on heat transfer performance of cryogenic sintered-wick heat pipe. (5th February 2019) - Sangpab, Nampon; Kimura, Nobuhiro; Terdtoon, Pradit; Sakulchangsatjatai, Phrut; Kammuang-lue, Niti; Murakami, Masahide
Highlights: Combined effect of bending and flattening on heat transfer performance was tested. Bending affects the performance by wick deformation that obstructs liquid flow. Flattening affects the performance by the collapse of wick and liquid clogging. Abstract: Heat transfer characteristics of a cryogenic sintered-wick miniature bent and flattened heat pipe has been experimentally investigated in this paper. The heat pipes are made of oxygen free copper for the container and nitrogen is used as the working fluid. The wick was composite wick made from sintered copper powder and grooved copper pipe. The original cylindrical copper heat pipe was 6 mm in outer diameter and 200 mm in length. The heat pipes with the bending radius of 21 mm and the bending angle of 0°, 30°, 60° and 90° and the final thickness of 2.5, 3.0, 4.0 mm were constructed and tested. The operating temperature of heat pipe was at approximately 78.25 ± 0.10 K. It was found that the performance of the heat pipe in terms of thermal resistances depends on both bending angle and final thickness. Both bending and flattening affect the thermal resistance by increasing it. The bending increased the thermal resistance from 0.88 to 1.07 K/W (6 mm, 0° to 6 mm, 90°) and the flattening increased the thermal resistance from 0.88 to 2.24 K/W (6 mm, 0° to 2.5 mm, 0°). And the combined effect of bending and flattening increased the thermal resistance from 0.88 to 1.56 K/W (6 mm, 0° to 3 mm, 90°). The bending affects heat pipe by wick deformation that obstructs liquid flow. The flattening affects the thermal resistance by the collapse of wick structure which causes a broken liquid path of returned working fluid from the condenser to the evaporator and by liquid clogging in the condenser.